In the shadow illegal markets and economic sociology - Jens Beckert; Frank Wehinger (Max Planck Institute for the Study of Societies, 2011)
Illegal markets differ from legal markets in many respects. Although illegal markets have economic significance and are of theoretical importance, they have been largely ignored by economic sociology. In this article we propose a categorization for illegal markets and highlight reasons why certain markets are outlawed. We perform a comprehensive review of the literature to characterize illegal markets along the three coordination problems of value creation, competition, and cooperation. The article concludes by appealing to economic sociology to strengthen research on illegal markets and by suggesting areas for future empirical research. – – Illegale Märkte unterscheiden sich in vielerlei Hinsicht von legalen Märkten. Trotz ihres großen wirtschaftlichen Gewichts und ihrer theoretischen Bedeutung blieben sie in der Wirtschaftssoziologie bislang weitgehend unbeachtet. Dieses Papier schlägt eine Kategorisierung illegaler Märkte vor und diskutiert die Gründe für ihr Verbot. Auf der Grundlage einer umfassenden Literaturauswertung werden die Strukturmerkmale illegaler Märkte anhand der drei Koordinierungsprobleme der Wertbildung, des Wettbewerbs und der Kooperation dargestellt. Das Papier schließt mit Empfehlungen für zukünftige empirische Forschung.
Keywords: 300; Schwarzmarkt; Wirtschaftssoziologie; Theorie